Communicative Language Teaching with Realia to Enhance Students’ English Vocabulary - Patmi, Resky Indrayana Uda; Sabaruddin, Sabaruddin (Universitas Islam Ahmad Dahlan (UIAD), 2021)
This research discusses vocabulary improvement of second year student at Madrasah Tsanawiyah Madani Pao-pao, South Sulawesi, Indonesia using Communicative Language Teaching with Realia. Researchers intend to answer the question